Psychopathic traits and identity threat as predictors of everyday heroism. (15th January 2020) - Bronchain, Jonathan; Raynal, Patrick; Chabrol, Henri
Abstract: Psychopathic traits and heroic behaviors seem to display atypical relationships. Some have argued that fearless temperament could underlie both psychopathic and heroic dispositions. However, the relative contribution of narcissism and identity threat has received little attention in explaining these behaviors. We hypothesized that individuals exhibiting psychopathic characteristics would be more prepared to perform heroic behaviors when they are motivated by extrinsic social rewards or punishment. Participants were 1050 college students who received measures of psychopathic traits (antagonism, disinhibition, narcissism, emotional stability), identity threat, and heroic behaviors. We presented correlation analysis and a structural equation model whereby the relations between these variables were analyzed. As expected, results demonstrated that identity threat, narcissism, and emotional stability predicted heroic behaviors. Identity threat mediated the link between narcissism and emotional stability dimensions and heroism. Our results provide a key to understand heroic behaviors in individuals exhibiting psychopathic traits.